University on the Border: Crisis of authority and precarity - Lange, Lis; Reddy, Vasu; Kumalo, Siseko H (African Sun Media, 2021)
The volume explores and thinks through the process of decolonising the South African higher education system by examining #MustFall. The text offers theoretical insights from a historical, contemporary and multidisciplinary lens, while examining the embedded meanings of the university as an institution, idea and set of practices to show the shifts and changes that were inaugurated by #MustFall along with the historicities that define the university both locally and globally. The retro- and prospective insights presented in the book surface the crisis of authority that places the university in a state of precarity, which is framed in the book as the ‘border’. The volume proposes the concept of the ‘border’ (recognising its conceptual and analytical dynamism) as a generative space that can facilitate new imaginaries and articulations of this social institution: the university.